Micro-Economic Impact and Consumptive Behavior Analysis of Millennial–Gen Z Individuals Entrapped in Online Gambling: A Qualitative Study in Bojonegara District, Serang–Banten - Bambang Dwi Suseno; Herlin Kurniawati; Ika Pratiwi; Basrowi Basrowi (Journal of Economic Education and Entrepreneurship Studies, 2026)
The rapid growth of digital technology has increased access to online gambling, enabling individuals to participate through computers or smartphones without physical or social constraints. This study examines the rising involvement of Millennial and Generation Z youth in online slot gambling in Bojonegara District, Serang–Banten, focusing on their motivations and the resulting economic and psychological impacts. Using a qualitative case-study approach, data were collected through in-depth interviews with ten adolescent gamblers, supported by participant observation and document review to enhance contextual depth and triangulation. Findings show that youth are primarily motivated by entertainment, the desire to relieve stress, and hopes of gaining quick financial rewards. However, the consequences are largely harmful, including significant financial losses, growing debt, heightened stress, anxiety, depressive symptoms, and weakened social and family relationships. These outcomes demonstrate that online slot gambling disrupts both the economic stability and psychosocial well-being of young people. The study’s novelty lies in its integration of micro-economic vulnerability with behavioral motivations among Millennial and Gen Z gamblers—an area rarely explored in the Indonesian context. The results also highlight how digital gambling platforms create addictive ecosystems that particularly appeal to younger users. The study emphasizes the urgency of stronger regulation, increased public awareness, and improved mental-health support to reduce the risks of online gambling among youth.